Answer:
{-110, -1100, -11000, -110000}
Explanation:
Recursive form of a sequence
A sequence is given in recursive form when the general term is written as a function of one or more previous terms, unlike the explicit form, which expresses the general term as a function of the first term and the common difference.
We are given the recursive formula:
f(1)=-11
f(n)=f(n-1)*10
This formula can only be valid for n>1. I'm adding this restriction to make it have sense because if n=1, we'd need f(0) and we don't have it.
The first four terms (apart from the given term are):
f(2)=f(2-1)*10=f(1)*10=-11*10=-110
f(3)=f(3-1)*10=f(2)*10=-110*10=-1100
f(4)=f(4-1)*10=f(3)*10=-1100*10=-11000
f(5)=f(5-1)*10=f(4)*10=-11000*10=-110000
Thus, the first four terms of the sequence are:
{-110, -1100, -11000, -110000}